DC Electric Field‐Enhanced Grain‐Boundary Mobility in Magnesium Aluminate During Annealing. Issue 6 (21st March 2016) - Rufner, Jorgen F.; Kaseman, Derrick; Castro, Ricardo H.R.; van Benthem, Klaus
Abstract : Magnesium aluminate spinel was sintered and annealed at 1300°C under an applied 1000 V/cm DC electric field. The experiment was designed such that current could be removed as a variable and just the effect of a noncontact electric field was studied. Enhanced grain growth was observed for both samples that were sintered or annealed after densification in the presence of an electric field. Grain‐boundary character distributions revealed that no microstructural changes were induced due to the field. However, the electric field was found to enhance the kinetic movement of cations within the lattice. Energy‐loss spectroscopy experiments revealed cation segregation resulting in regions of Mg‐rich and Al‐rich layers adjacent the grain‐boundary cores. The defects generated during segregation supported the generation of a space charge gradient radiating from the grain‐boundary core out into the bulk, which was significantly affected by the applied field. The interaction between the field and space charges effectively reduced the activation energy for cation movement across boundaries thereby enhanced grain‐boundary mobility and resultant grain growth.